2020
DOI: 10.1140/epja/s10050-020-00237-2
|View full text |Cite
|
Sign up to set email alerts
|

Charged-pion production in $$\mathbf {Au+Au}$$ collisions at $$\sqrt{\mathbf {s}_{\mathbf {NN}}} = 2.4~{\mathbf {GeV}}$$

Abstract: We present high-statistic data on charged-pion emission from Au + Au collisions at $$\sqrt{s_{\mathrm{NN}}} = 2.4~\hbox {GeV}$$ s NN = 2.4 GeV (corresponding to $$E_{beam} = 1.23~\hbox {A GeV}$$ E beam = 1.23 A GeV ) in four centrality classes in the range 0–40% of the most central collisions. The data are analyzed as a function of transverse momentum, transverse mass, rapidity, and polar angle. Pion multiplicity per participating nucleon decreases moderately with increasing centrality. The pola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…In Ref. [30], we had shown that a proper description of the transverse-mass spectrum requires in fact the sum of two Boltzmann distributions, expressed as…”
Section: Coulomb Field Acting On Charged Pionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Ref. [30], we had shown that a proper description of the transverse-mass spectrum requires in fact the sum of two Boltzmann distributions, expressed as…”
Section: Coulomb Field Acting On Charged Pionsmentioning
confidence: 99%
“…( 4) -( 6) in the energy sampling routine. In the simulation, we have set the parameters to T 1 = 50 MeV, T 2 = 90 MeV, f = 0.95, V c = 15 MeV, and T p = 130 MeV which are typical values observed for the energy regime where HADES operates [30,32]. The left panel of Fig.…”
Section: Effect On the Kinematic Distribution Of Charged Pionsmentioning
confidence: 99%
See 3 more Smart Citations